Partisipasi Politik Masyarakat pada Pemungutan Suara Ulang Pilkada Serentak 2024 Berdasarkan Putusan Mahkamah Konstitusi Republik Indonesia Nomor 132/PHPU.BUP-XXIII/2025 di Kabupaten Tasikmalaya Perspektif Siyasah Dusturiyah - Muhammad Fauzan; Bobang Noorisnan Pelita; Lutfi Fahrul Rizal (CV Rewang Rencang, 2025)
This study examines community political participation in the 2024 Simultaneous Regional Election Re-Vote (PSU) in Tasikmalaya Regency, based on the Constitutional Court Decision of the Republic of Indonesia Number 132/PHPU.BUP-XXIII/2025, from the perspective of Siyasah Dusturiyah. As a manifestation of popular sovereignty, regional elections must ensure the active participation of the public. The Tasikmalaya Regency General Election Commission (KPU) has attempted to implement a responsive legal approach through outreach activities and stakeholder engagement, in accordance with Article 26 of KPU Regulation Number 9 of 2022. However, voter turnout in the re-vote was only 63.4%, a decline of 4.5% from the previous election. This low level of participation was due to several field implementation challenges, including the re-vote period coinciding with the post-Eid al-Fitr return flow and high urban mobility; the very short KPU socialization period (60 days) with minimal intensity in remote areas; declining public trust following previous election violations; and issues with the accuracy of the Final Voter List (DPT), such as unupdated records of deceased voters. From the Siyasah Dusturiyah perspective, this phenomenon indicates the suboptimal application of the principles of shura (consultation), ‘adl (justice), and ijma’ al-ummah (public consensus), suggesting the presence of a